Nome waterfront showing lightering operation, August 1905 - Nowell, Frank H., 1864-1950 (1905)
Caption on image: Nome Improvement Co., Aug. 9th 1905, showing first day's work of Longshoremen's Union, Nome, Alaska. Photo by F.H. Nowell, 4084 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number